FROM WITNESS TO WOUNDED: HOW CYBERBULLYING POISONS THE PEER ECOSYSTEM OF A MALAYSIAN UNIVERSITY CAMPUS - Md Yusof, Nor Fadzilah; Wan Abu Bakar, Wan Hashridz Rizal (Jurnal 'Ulwan, 2025)
This phenomenological study explores the lived experiences of ten undergraduates at Universiti Islam Pahang Sultan Ahmad Shah who witnessed or experienced cyberbullying. Through semi-structured interviews, four interlocking themes emerged: profound psychological distress, social withdrawal, academic-cognitive disruption, and defensive digital behaviour. Fear, shame and rumination spread rapidly from targeted students to witnesses, eroding self-esteem, friendship networks and classroom concentration. Victims muted chats, deactivated accounts and self-censored, shrinking both social presence and academic participation. The findings frame cyberbullying as an ecological toxin that poisons the entire peer ecosystem rather than isolated individuals. To counteract this systemic risk, the paper recommends a 24-7 rapid-response team integrating counsellors, academics and IT staff; compulsory digital-citizenship modules; encrypted in-app reporting; and peer-led “digital defenders.” National-level advocacy for a dedicated Cyberbullying Act and platform accountability mechanisms is urged. Limitations include single-site, retrospective, female-majority sampling; multi-campus quantitative and longitudinal designs are proposed to establish prevalence, causality and protective factors.